2016 IEEE 55th Conference on Decision and Control (CDC) 2016
DOI: 10.1109/cdc.2016.7799284
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pointing tasks in mouse-based human-computer interactions

Abstract: Pointing is a basic gesture performed by any user during human-computer interaction. It consists in covering a distance to select a target via the cursor in a graphical user interface (e.g. a computer mouse movement to select a menu element). In this work, a dynamic model is proposed to describe the cursor motion during the pointing task. The model design is based on experimental data for pointing with a mouse. The obtained model has switched dynamics, which corresponds well to the state of the art accepted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The most thorough investigations of transfer functions in HCI are by Casiez et al In [7], they compare movement times in reciprocal pointing for static gains (1,2,4,6,8,12) and six levels for the PA function implemented in Windows XP/Vista. They find that PA results in 3.3% faster pointing, and 5.6% for small targets.…”
Section: Current Understanding Of Transfer Functions In Hcimentioning
confidence: 99%
See 2 more Smart Citations
“…The most thorough investigations of transfer functions in HCI are by Casiez et al In [7], they compare movement times in reciprocal pointing for static gains (1,2,4,6,8,12) and six levels for the PA function implemented in Windows XP/Vista. They find that PA results in 3.3% faster pointing, and 5.6% for small targets.…”
Section: Current Understanding Of Transfer Functions In Hcimentioning
confidence: 99%
“…It was shown that the resulting model is stable under any PA function, and theoretical performance bounds of the model have been derived. [1] propose an extension of the VITE model with Bang-bang control. When the error is large, Bang-bang control is used, and VITE is used for corrections close to the target.…”
Section: Dynamical Systems Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The abridged version of this paper appeared in [36]. The main added values of this submission are: 1) Proposition 1 of this manuscript is stronger than the one of [36]; 2) the proof of Proposition 3 is not given in [36]; 3) significantly extended experimental and numerical results; 4) a comparison against pointing models available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…There exist several dynamic models of human movements, e.g. the open-loop minimum-jerk optimal model used in [6], and the recently proposed dynamic models for indirect humancomputer interaction [7], [8]. However, these models are valid for specific pointing movements only and cannot be applied for general direct interaction.…”
Section: Introductionmentioning
confidence: 99%